Analisis Studi Kelayakan Bisnis pada Usaha Es Teh “Teh Kaling” - Dzilla Khoerunnisa; Wahidah Nazmi Lailia; Aufa Zulfikar Maulana; Perwito Perwito (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
“Teh Kaling” is a drink that combines the iconic taste of tea with kolang kaling topping. Kolang kaling is processed from half ripe palm fruit that has been burned of boiled. Apart from creating viable business results in terms of management, marketing, financial, operational and environmental impact aspects. The research was also carried out to show that kolang kaling can be used as a main topping in tea drinks. The data obtained comes from market surveys and interviews with potential consumers. This business has high prospects, considering that kolang kaling has high nutritional value and is unique in combining it with fresh tea drink.